2019
DOI: 10.3389/fphys.2019.01490
|View full text |Cite
|
Sign up to set email alerts
|

Core Endurance Relationships With Athletic and Functional Performance in Inactive People

Abstract: Research regarding the relationship between core muscle endurance and performance is limited. The purpose of this study was to analyze the association between core/trunk endurance and athletic performance. Seventy-four healthy participants between 18 and 45 years old participated in this study (Age: 26.0 ± 6.5 years; Mass: 74.6 ± 12.8 kg; Height: 1.74 ± 0.08 m; BMI: 19.0 ± 6.8 kg/m 2). The core endurance was measured using the McGill protocol, consisting of the following tests: trunk flexion, back extension, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Since poor posture can affect joints, bony structures, and soft tissues, resulting in musculoskeletal disorder [18], therefore, it seems logical to use the FMS score as a postural assessment tool. Among several methods of core muscle assessment, the McGill test is the most reliable isometric test to evaluate core muscle endurance and stability [19] which is used in previous studies in a different age of people with different levels of physical activity [20][21][22]. As mentioned above, there seems to be a direct relationship between posture and lumbopelvic stability [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since poor posture can affect joints, bony structures, and soft tissues, resulting in musculoskeletal disorder [18], therefore, it seems logical to use the FMS score as a postural assessment tool. Among several methods of core muscle assessment, the McGill test is the most reliable isometric test to evaluate core muscle endurance and stability [19] which is used in previous studies in a different age of people with different levels of physical activity [20][21][22]. As mentioned above, there seems to be a direct relationship between posture and lumbopelvic stability [8].…”
Section: Introductionmentioning
confidence: 99%
“…The side plank exercise evaluates the endurance of abdominal muscles against constant resistance while maintaining the body posture. [ 4 , 33 , 34 ] The time required for the SCST is shorter (<10 seconds). Although both measures are used to evaluate core stability, the different processes and aims render the results incompatible.…”
Section: Discussionmentioning
confidence: 99%
“…Core stability has been described as the product of motor control and muscular capacity of the lumbopelvic-hip complex. [1][2][3][4][5] Many studies have reported that core stability is essential to reduce low back pain. [6][7][8][9][10] Therefore, core stability and core strength training are elements of rehabilitation programs.…”
Section: Introductionmentioning
confidence: 99%
“…Core endurance refers to the ability to maintain a static posture or perform repetitive movements for a long period of time [7,8]. Improved core endurance can increase the time to maintain the core stable, which can increase the time to transmit or generate force from the trunk to the upper and lower extremities while performing sports or daily living activities [9]. Therefore, core strength and endurance are considered important factors in core stability.…”
Section: Introductionmentioning
confidence: 99%